On the Gracefulness of Graph $(jC_{4n}) ∪ P_m$ (Communications in Mathematical Research, 2021)
The present paper deals with the gracefulness of unconnected graph$(jC_{4n}) ∪ P_m$, and proves the following result: for positive integers $n$, $j$ and $m$ with $n ≥ 1$, $j ≥ 2$, the unconnected graph $(jC_{4n}) ∪ P_m$ is a graceful graph for $m = j − 1$ or $m ≥ n + j$, where $C_{4n}$ is a cycle with $4n$ vertexes, $P_m$ is a path with $m + 1$ vertexes, and $(jC_{4n}) ∪ P_m$ denotes the disjoint union of $j − C_{4n}$ and $P_m$.
Keywords: graceful labeling; graceful graph; path; cycle; disjoint union.